Pulmonary congestion and systemic congestion in hemodialysis: dynamics and correlations - Kaysi, Saleh; Pacha, Bakhtar; Mesquita, Maria; Collart, Frédéric; Nortier, Joëlle (Frontiers in Nephrology, 2024)
Systemic congestion and pulmonary congestion PC are common in Haemodialysis HD patients. However, the relation between these two entities is not quite clear. Here we study this relation and try to find out the factors that may affect it considering different inter-dialytic intervals.A prospective pilot observational and interventional study including 18 HD patients.We obtained: 1-B-lines scores (BLS) by Lung Ultrasound (LUS) (Reflecting a significant pulmonary congestion if BLS>5), 2-echocardiography, 3-bioelectrical impedance analysis (BIA) (reflecting global volume status), and 4-inferior vena cava (IVC) dynamics (reflecting systemic congestion) before and after the first two consecutive HD sessions of the week,Then patients were randomized into two groups: Active group: where dry weight was reduced according to BLS + standard of care, and Control group where dry weight was modified according to standard of care. We repeated all the measures at day 30.We found no correlation between pulmonary congestion represented by BLS and IVC dimensions and dynamics reflecting systemic congestion. Pulmonary congestion was quit prevalent.Pulmonary congestion was correlated to BIA only in the second HD session (HD2) (R²= 0.374, P= 0.007). Systemic congestion was quit prevalent, with a higher level of systemic congestion in the first HD session; (Diameter, Collapsibility).IVC dimensions and BIA were correlated in the second dialysis session (R²=0.260, P=0.031)..At day 30, BLS was significantly reduced in the active group, whereas no difference was found in the control group. However, no real impact was observed on IVC dimensions and dynamics or in BIA. Pulmonary congestion is common in HD patients even after reaching their dry weight at the end of two consecutive sessions, and it is not correlated to systemic congestion, suggesting a complex multifactorial pathophysiology origin. Global volume status reflected and cardiac function are not always related to either systemic congestion represented by IVC dimensions or to pulmonary congestion. Fluid redistribution anomalies may allow pulmonary congestion independently from systemic congestion and global volume status.We recommend a personalised approach when managing HD patients integrating systemic and pulmonary congestion. Dry weight modification guided by repeated LUS may safely reduce pulmonary congestion. However, no impact was noticed on systemic congestion or global volume status.